Curriculum “Sekolah Penggerak”: An Overview of Solutions to Learning Problems - Magdalena, Maulida Cindy (Proceeding International Conference on Religion, Science and Education, 2022)
Some of the problems found in the 2013 curriculum include understanding and applying scientific approaches, understanding learning integration, material levels, and time constraints. Currently, the Indonesian ministry of education and culture is developing a program called “Sekolah Penggerak”. This program performs several concepts in many aspects to answer these problems. These differences are found in the learning time, learning stages, and competencies that must be achieved by students. It shows that the “sekolah penggerak” programme focused more on essential and fundamental learning processes. Based on documents and theoretical studies, the “sekolah penggerak” program can answer several problems such as limited time and material levels. But solutions to other problems such as scientific approach problems were not found. However, further studies on the concept and implementation of “sekolah penggerak” are still needed.